Impact of Long-Term Cold Storage on the Physicochemical Properties, Volatile Composition, and Sensory Attributes of Dried Jujube (Zizyphus jujuba Mill.) - Shaoxiang Pan; Xuemei Liu; Xiaodong Zheng; Jihong Wu; Mengnan Tan; Ning Cao; Xinyu Zhao; Maoyu Wu; Yu Han; Xinhuan Yan; Ye Song (Foods)
Grey jujube (Zizyphus jujuba Mill. cv. Huizao), a prominent cultivar from Xinjiang, China, is well known for its high nutritional value and medicinal benefits. This study investigates the effects of long-term storage on the quality attributes of grey jujube, focusing on color, texture, physicochemical properties, bioactive ingredients, amino acid profiles, sensory characteristics, and volatile compounds. Over a three-year storage period, significant changes were observed, including a decline in lightness and redness of the peel, accompanied by textural modifications such as increased hardness and chewiness, primarily attributed to moisture loss. Physicochemical analyses revealed significant reductions in moisture content, sugars (particularly reducing sugars), and bioactive compounds such as vitamin C, total flavonoids, and cyclic adenosine monophosphate (cAMP). In contrast, total acidity showed a significant increase over time. Sensory evaluation indicated a substantial loss of fresh aroma and flavor, with the development of off-flavors over time. Additionally, a comprehensive analysis of volatile compounds highlighted significant transformations in aroma profiles, with notable reductions in desirable esters and increases in acetic acid concentrations. This study investigates the quality changes of grey jujubes during storage from sensory and physicochemical perspectives, aiming to provide a novel approach for differentiating between newly harvested and aged grey jujubes. Furthermore, these findings provide theoretical support for improving and optimizing storage conditions. Future research should focus on elucidating the underlying mechanisms of these changes, identifying key markers for quality control during grey jujube storage, and providing a scientific basis for distinguishing between newly harvested and aged grey jujubes, while improving storage quality.